Nowe wyzwania dla odpowiedzialności deliktowej przewidzianej w polskim prawie — wybrane uwagi w związku z funkcjonowaniem tak zwanych pojazdów autonomicznych - Kuźmicka-Sulikowska, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The article briefly presents the key aspects of the current solutions of Polish civil law regulating liability for damages caused by the movement of mechanical means of communication moved by forces of nature. Against this background, considerations have been made as to whether these regulations will remain adequate in relation to the movement of fully autonomous vehicles, the introduction of which to the market will be announced in the near future. It is indicated what is understood as an autonomous car and what are the levels of automation of this type of cars. It has been shown that some existing rules on liability for damage caused by car traffic will not be adequate to attribute responsibility for damage caused by fifth level autonomous cars; other rules, however, can be used with appropriate modification of their interpretation. However, an appropriate amendment to the regulations to adapt them to the specificity of such fully autonomous vehicles is not excluded. Selected problem issues that may appear in this context are also shown.
Keywords: odpowiedzialność cywilna; wypadki samochodowe; samochody autonomiczne; odpowiedzialność oparta na zasadzie ryzyka